ANALISIS KRITIS NEOCLASSICAL REALISM: STUDI KASUS INVASI RUSIA TERHADAP UKRAINA PERIODE (2022) - Surur, Nadirah; Ariaputra, Alif (Universitas Prof. Dr. Moestopo (Beragama), 2023)
The Russian invasion of Ukraine in 2022 has reignited debate on global security and foreign policy behavior of great powers. This study analyzes the underlying drivers of Russia's foreign policy decisions using a three-level theoretical framework. At the grand theory level, classical realism explains the anarchic nature of international politics and the centrality of power. At the middle theory level, Neoclassical Realism (NCR) is applied to link systemic pressures with domestic variables—particularly elite perceptions and strategic culture. At the applied level, the concept of overbalancing is used to explain Russia’s aggressive posture. Utilizing a qualitative method and literature review, the study examines government documents, academic journals, and institutional reports. Findings show that Russia’s invasion was shaped not only by NATO’s perceived encroachment but also by internal political needs to reinforce regime legitimacy. This research highlights the explanatory power of NCR in capturing the complexity of state behavior that cannot be fully explained by systemic-level analysis alone. The study contributes to foreign policy literature by offering a multidimensional understanding of aggression in contemporary international relations.